A gender comparative analysis of post-traumatic stress disorder among a community-based cohort of people who use drugs in Vancouver, Canada. (April 2021) - Mitra, Sanjana; Lee, William; Hayashi, Kanna; Boyd, Jade; Milloy, M.J.; Dong, Huiru; Wood, Evan; Kerr, Thomas
Highlights: Women who use drugs reported a higher prevalence of PTSD compared to men. In women, violence and higher intensity drug use were associated with PTSD. Both women and men reported high proportions of PTSD symptoms across all clusters. Abstract: Background: While exposure to traumatic events and subsequent post-traumatic stress disorder (PTSD) are common among people who use drugs (PWUD), little is known about gender-based differences associated with PTSD in this population. We explore gender-based differences in factors associated with a probable PTSD diagnosis in a cohort of PWUD from Vancouver, Canada. Methods: Data were collected through the Vancouver Injection Drug Users Study (VIDUS) and the AIDS Care Cohort to Evaluate Exposure to Survival Services (ACCESS), two community-recruited cohorts of PWUD. Participants were administered the PTSD Checklist for DSM-5. Multivariable logistic regression was used to investigate social-structural factors and substance use patterns and behaviours associated with a probable PTSD diagnosis, stratified by self-identified gender. PTSD symptom clusters and brief descriptions of the worst traumatic event experienced were also reported. Results: Between December 2016 and December 2018, of 797 eligible participants, 295 (37.0%) identified as women. PTSD was more commonly reported in women compared to men (53.2% vs. 31.5%, p < 0.001). In multivariable analysis involving men, no correlates were associated with PTSD. In multivariable analysis involving women, PTSD was positively associated with exposure to violence (AOR: 3.66; 95%CI: 1.14–11.72), daily stimulant use (AOR: 2.32; 95%CI: 1.32–4.08) and heavy alcohol use (AOR: 3.84; 95%CI: 1.84–8.00), and negatively associated with being in a stable relationship (AOR: 0.46; 95%CI: 0.25–0.84). Conclusions: Gender-based differences in PTSD diagnosis among a cohort of PWUD point to the need to develop gender-focused and trauma-informed health and social services to meet the immediate needs of PWUD living with PTSD.